Group A Streptococcus pharyngitis among schoolchildren in Mbulu District, Tanzania - Makuka, Fatuma; Mwakalinga, Steven; Mattaka, Hassan; Kipanyula, Maulilio; Manjurano, Alphaxard (Tanzania Journal of Health Research, 2016)
Streptococcal pharyngitis continues to be one of the most common childhood illnesses throughout the world. Recent evidence indicates an increased incidence of group A Streptococcal (GAS) infections, which is a significant cause of mortality and morbidity on the global scale. The objective of this study was to determine prevalence of group A Streptococcus infection among primary schoolchildren in Mbulu district, northern Tanzania. This study was carried out in five primary schools, namely Mangisha, Gunyoda, Kainam, Hyloto and Tsaayo. GAS pharyngitis was diagnosed clinically and confirmed by laboratory investigation using a rapid test. A total of 320 study participants were recruited in the study. Overall, more than half (53.8%) of the children were females. The overall prevalence of Group a Streptococcal infection was 6.9% (95%CI [4.4-10.2]). The highest frequency of GAS infection was observed among children at Hyloto primary school (14.3%) while, none of the children in Tsaayo had GAS infection. This study potentially indicates that group A Streptococcal infection prevalent among schoolchildren in Mbulu district calling for the need of education to create awareness of the condition in the community.